STRATEGIES TO IMPROVE THE QUALITY OF HIGHER EDUCATION SYSTEM (Web of Teachers: Inderscience Research, 2024)
Higher education is an essential component of individual and societal progress. Through higher education, individuals can acquire in-depth knowledge and specialized skills in a variety of disciplines like critical thinking, problem-solving skills, presentation skills, communications skills, teamwork and leadership skills, which are highly valued in the modern job market. Therefore, higher education is essential for personal development, professional success, societal progress, and the advancement of knowledge and innovation.This article discusses about some strategies to improve the quality of higher education system and their impact on economy.